ANALYSIS OF SHOPEEFOOD SERVICES IN INCREASING SALES IN KULINER IN KUDUS CITY - Triana Hasty Kusuma (Sean Institute, 2022)
One of the most popular e-commerce sites in Indonesia, Shopee, has launched a food-delivery service called ShopeeFood which can be accessed via smartphone applica- tion, making it easier for Indonesians to order food from abroad. As a newcomer to the food delivery industry, ShopeeFood's prices are higher than its competitors. The purpose of this research is to study and analyze the contents of the ShopeeFood platform to help the local food market in Kudus City grow faster than it already is. This research used a probability sampling technique with a total of 50 participants. The ShopeeFood service in Kudus was used as a test case for this Iitian. This research shows that ShopeeFood services have a significant effect on increasing culinary sales in Kudus.